Beeja Chatushtaya - A Special Unique Contribution of Sushruta Samhita (International Journal of Ayurveda and Pharma Research, 2023)
Beeja Chatushtaya or Chikitsa Chatustaya is an important unique methodology explained by Acharya Sushruta. It is the fundamental principle that establishes the foundation for the Sushruta Samhita. On the basis of this principle, the whole Shusruta Samhita has been developed. Beeja Chatushtaya includes Purusha (individual person), Vyadhi (diseases), Aushadha (medicine) and Kriyakaal (time of administration of treatment). Purusha is believed to be the combination of Panchamahabhuta and Atma. Karma Purusha provides Adhishtana and Ashraya for Vyadhi and Chikitsa. Every type of Shareerika, Manasika, and Agantuja Vedana are included in the Roga, Dukkha, or Vedana. Dukkha Nivrutti can be obtained through administration certain drugs and other procedures are used to implement certain Kriya or Chikitsa principles. In Beeja Chatushtaya Kriya, Swasthanuvartana chikitsa, Snehanadi karma, and Shastradi karma are all mentioned. Snehapana in Prabhatakaal, Swedana jeernaanna Kaal, Vamana in Purvahna, Virechana in Prataha Kaal, Asthapana in Madhyahna Kaal, and Anuvasana in Sayankaal (Pradosha Kaal after meal) are examples of Kaal. Kaal also refers to Avasthika Kaal, such as Langhana in Jwara's samavastha and Ghritapana in Jeerna jwara avastha. In this article, an attempt has been made to analyse the various measures and concepts of Beeja Chatushtaya described in a dispersed manner in Sushruta Samhita, which are collected, compiled and discussed.